Imaging the Premonitory Phase of Migraine - Karsan, Nazia; Goadsby, Peter J. (Frontiers in Neurology, 2020)
Migraine is a common and disabling brain disorder with a broad and heterogeneous phenotype, involving both pain and non-pain symptoms. Over recent years, more clinical and research attention has been focused towards the premonitory phase of the migraine attack, which can start up to days before the onset of head pain. This early phase can involve symptomatology such as cognitive and mood change, yawning, thirst and urinary frequency, as well as sensory sensitivities, such as photophobia and phonophobia. In some patients, these symptoms can warn of an impending headache, and therefore offer novel neurobiological and therapeutic insights. As well as characterization of the phenotype of this phase, recent studies have attempted to image this early phase using functional neuroimaging, to attempt to understand how the symptoms are mediated and how a migraine attack may be initiated, and how nociception may follow thereafter. This review will summarise the recent and evolving findings in this field, and hypothesise a mechanism of subcortical and diencephalic brain activation during the start of the attack, including that of basal ganglia, hypothalamus and thalamus, prior to headache, which causes a top down effect on brainstem structures involved in trigeminovascular nociception leading ultimately to headache.